STUDI TENTANG ENTREPRENEURAL SELF EFFICACY DAN PROACTIVE PERSONALITY, SERTA PENGARUHNYA TERHADAP ENTREPRENEURAL INTENTION - Prima Naomi; Ayu Dwi Nindyati (Universitas Trisakti, 2009)
The purpose of this study was to know the grade level of entrepreneural intention among Paramadina's student, and to investigate the affecting role of Entrepreneurial Self Efficacy and Proactive Personality to Entrepreneural Intention, The subject of the study is the Paramadina Student who has taken entrepereneurship subject. The author used proportional cluster sampling and analyze done by decscriptive statistics and multiple regression analysis.The results showed that entrepreneurial intention among students is moderately high and all of variable of this research were significantly affecting to Entrepreneural Intention. The results strenghthen the previous research, that has proven both practical and theoretical implication. The theoretical implication showed that needed to investigate the proactive personality variable within other research subject and consider to use of moderate variable which can multiply the effect of proactive personalty toward entrepreneurial intention. The practical implication was suggested by applying the learning process toward developing entrepreneur self efficacy.Keywords : Entrepreneural intention, Entrepreneur& self efficacy, Proactive personality